Menelisik Falsafah Nrimo Ing Pandum pada Manajemen Desa Wisata Ketingan, Sleman - Prayoga, I Ketut Aditya; Yahya, Azfa Naufal; Tarwaca, Muammar Iqbal Khadafi (JURNAL NASIONAL PARIWISATA, 2024)
The philosophy of nrimo ing pandum is a concept of accepting fate in Javanese culture which is often misinterpreted as a fatalistic and resigned attitude. This research aims to reveal misconceptions about cultural values, namely the nrimo ing pandum philosophy which has become a fatalistic culture in the community managing tourist villages in Sleman Regency, then linking this to the case of stagnation in Ketingan Tourism Village, Sleman Regency, DIY in tourism destination management. Qualitative descriptive methods were used with data collection carried out through non-participatory observation and interviews with research subjects, namely the local community of Ketingan Tourism Village. The data obtained was then analyzed using categorization according to themes arranged based on the initial hypothesis. The results show that people's misconceptions about the true meaning of the nrimo ing pandum philosophy play a role in the stagnation of tourism village development. The fatalistic mindset that accompanies it makes it difficult for them to innovate and rise from stagnation even though they have entered a phase of decline. Poor destination management also plays a role in causing stagnation in this tourist village. So, it is necessary to transform the community's mindset regarding the true meaning of philosophy as well as increasing the capacity of tourism village managers through various training. Apart from that, policies and programs from the regional government are really needed so that the Ketingan Tourism Village can recover from tourism stagnation and develop again.